2015
DOI: 10.1039/c4cp05972g
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of the GaAs semiconductor at the Al2O3/GaAs junction

Abstract: Atomic-scale understanding and processing of the oxidation of III-V compound-semiconductor surfaces are essential for developing materials for various devices (e.g., transistors, solar cells, and light emitting diodes). The oxidation-induced defect-rich phases at the interfaces of oxide/III-V junctions significantly affect the electrical performance of devices. In this study, a method to control the GaAs oxidation and interfacial defect density at the prototypical Al2O3/GaAs junction grown via atomic layer dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…26 Thus, GaSb(100)(1 Â 3)-In-O is a hitherto unreported member for the crystalline oxidized III-V surfaces, 27 which have been shown to potentially decrease the defect densities at insulator/III-V interfaces. [28][29][30] The density of disorderinduced point defects can also be expected to decrease on GaSb(100)(1 Â 3)-In-O, but it is still unclear what kind of band structure is formed in the building block(s) of GaSb(100)(1 Â 3)-In-O itself, in relation to the GaSb band gap area. To clarify this, a comparison of the STS curves of GaSb(100)(4 Â 3) and (1 Â 3)-In-O is shown in Fig.…”
mentioning
confidence: 99%
“…26 Thus, GaSb(100)(1 Â 3)-In-O is a hitherto unreported member for the crystalline oxidized III-V surfaces, 27 which have been shown to potentially decrease the defect densities at insulator/III-V interfaces. [28][29][30] The density of disorderinduced point defects can also be expected to decrease on GaSb(100)(1 Â 3)-In-O, but it is still unclear what kind of band structure is formed in the building block(s) of GaSb(100)(1 Â 3)-In-O itself, in relation to the GaSb band gap area. To clarify this, a comparison of the STS curves of GaSb(100)(4 Â 3) and (1 Â 3)-In-O is shown in Fig.…”
mentioning
confidence: 99%
“…Figure shows the PL spectra for each of the samples along with the LEED figures of the starting surface of GaAs(100)(6 × 6) and the observed intense (1 × 1)‐InO x as insets. For LEED patterns of the other surfaces, we refer to our previous works . The least amount of nonradiative recombination is observed for the c (4 × 2) sample, and the most for the (1 × 1) sample.…”
Section: Interface Analysismentioning
confidence: 99%
“…Indeed, the nature of these interface defects and the methods to control their formation have been the subject of a vast body of investigations (e.g., refs. ). In previous studies, these defect states have been found to arise, among others, from group‐V dimers; group‐V and group‐III dangling bonds; and III‐Ox or V‐Ox phases.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations